Az „Oxford Group mozgalom” recepciója a királyhágómelléki sajtóban. Adalékok a KRE történetéhez - PÁLFI, József (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
Reception of the Oxford Group movement in the Királyhágómellék media. Contributions to the KRE history. The interwar period brought multiple challenges at every level to the newly formed Királyhágómellék Reformed Church District. After World War I, the district faced challenges to fill a given frame with a proper content. Establishing church in-stitutions on various levels and structuring internal mission were of highest priori-ties. The Oxford Group came as a new internal mission element to revitalise the Church, besides traditional approaches. However, the promoter of the organization failed to provide the Group a wider recognition. This study reveals the background of his efforts.